(untitled) (AIUB Journal of Science and Engineering (AJSE), 2024)
ZnO is widely used as a semiconductor material due to its wide bandgap, high exciton binding energy, and excellent transparency in the visible range, which make it suitable for optoelectronic applications. Doping in ZnO is important because it allows for controlling its electrical properties, enables the tuning of conductivity, and enhances its functionality for specific applications. Doping can introduce new energy levels within the bandgap. Moreover, it improves the performance of ZnO-based devices. This study explored the structural, optical, and electronic properties of pure and Praseodymium ion (Pr3+) doped ZnO using GGA+U based DFT. Results agreed with prior research, showing compatible lattice parameters and band gap for pure ZnO. Increasing Pr concentration expanded lattice parameters and volumes while reducing the energy band gap. Pr doping shifted the Fermi level to the upper conduction band, causing an overlap between the conduction and valence bands. This indicated a transition from a semiconductor to an n-type degenerate semiconductor with metal-like characteristics. Higher doping concentrations led to a shift in density of states towards lower energies. Computed optical properties exhibited red shifts in absorption peaks and increased absorption in the near and far ultraviolet regions following Pr doping. Similar red shifts were observed in the reflectivity spectrum and other optical properties. The real dielectric constant (ε1 (ω)) displayed negative values, signifying metallic behavior at specific photon energies, consistent with band structure optimization.